The Biodegradability and in Vitro Cytological Study on the Composite of PLGA Combined With Magnesium Metal - Wang, Xue; Sun, Hui; Song, Mang; Yan, Guangqi; Wang, Qiang (Frontiers in Bioengineering and Biotechnology, 2022)
The main goal of this study was to develop a novel poly (lactic-co-glycolic acid) (PLGA) composite biodegradable material with magnesium (Mg) metal to overcome the acidic degradation of PLGA and to investigate the cytocompatibility and osteogenesis of the novel material. PLGA composites with 5 and 10 wt% Mg were prepared. The samples were initially cut into 10 mm×10 mm films, which were used to detect the pH value to evaluate the self-neutralized ability. Murine embryo osteoblast precursor (MC3T3-E1) cells were used for in vitro experiments to evaluate the cytotoxicity, apoptosis, adhesion, and osteogenic differentiation effect of the composite biodegradable material. pH monitoring showed that the average value of PLGA with 10 wt% Mg group was closer to the normal physiological environment than that of other groups. Cell proliferation and adhesion assays indicated no significant difference between the groups, and all the samples showed no toxicity to cells. As for cell apoptosis detection, the rate of early apoptotic cells was proportional to the ratio of Mg. However, the ratios of the experimental groups were lower than those of the control group. Alkaline phosphatase activity staining and quantitative real-time polymerase chain reaction demonstrated that PLGA with 10 wt% Mg could effectively improve the osteogenic differentiation of MC3T3-E1 cells. In summary, PLGA with 10 wt% Mg possessed effective osteogenic properties and cytocompatibility and therefore could provide a wide range of applications in bone defect repair and scaffold-based tissue engineering in clinical practice.